2014
DOI: 10.1016/j.jclepro.2013.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Controversy over antibacterial silver: implications for environmental and sustainability assessments

Abstract: a b s t r a c tThe potential risks and benefits of using silver, especially nanosilver, as an antibacterial agent in consumer and healthcare products are under debate globally. Using content analysis of texts from newspaper and TV, government agencies, municipalities, government and parliament, non-governmental organizations, and companies, we analyze the argumentation in the Swedish public controversy over antibacterial silver and relate the findings to environmental and sustainability assessments. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Figure 1 provides a summary of the most widely voiced primary ideas and their rationales. It can be noted that these rationales correlate well with arguments identified in a previous study of antibacterial silver as a risk issue, including high/low toxicity, high/low exposure, low amount/quantity, and similarity to harmful substances (in that case mercury) [ 59 ].
Fig.
…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 1 provides a summary of the most widely voiced primary ideas and their rationales. It can be noted that these rationales correlate well with arguments identified in a previous study of antibacterial silver as a risk issue, including high/low toxicity, high/low exposure, low amount/quantity, and similarity to harmful substances (in that case mercury) [ 59 ].
Fig.
…”
Section: Resultssupporting
confidence: 74%
“…In addition to associations between graphene and risk, we are interested in the arguments that support such risk claims and we therefore identify the rationales communicated [ 59 ]. Some responses by the respondents were found to follow a risk/no-risk rhetoric as described by Corvellec and Boholm [ 60 ] and therefore categorized accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Ag NPs discharged to the wastewater stream were shown to be sulfidized to varying degrees and to be largely aggregated with biomass and biosolids [ 24 , 25 , 27 ]. Although there is clearly controversy on the risks and benefits of Ag NP containing consumer and healthcare products [ 41 ], the global impact of Ag NPs to WWTPs ( i.e. , therefore their actual toxicity in CWs) may be limited at the present time [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings clearly demonstrate that it is indeed possible to have a much greener way to synthesize SNPs without compromising their antibacterial properties and thus plant extracts may prove to be a good alternative to obtain such NPs with improved antibacterial and antiviral properties for diabetic wound healing applications. Goix et al 33 and Boholm and Arvidsson 34 have pointed out that silver is either beneficial or harmful in relation to four main values: the environment, health, sewage treatment, and product effectiveness. As reported by Barua et al 35 poly(ethylene glycol)-stabilized colloidal SNPs showed the nonhazardous anticancer and antibacterial properties.…”
mentioning
confidence: 99%